Keruntuhan Perancah Scaffolding Saat Pelaksanaan Pengecoran - Sumargo, Sumargo; Nata, Ario Raja (MEDIA KOMUNIKASI TEKNIK SIPIL, 2006)
In the construction process either for multy story building or structure with large horizontal coverage area, the selection of formwork construction is very essential. The acceleration of assemblying – deassemblying – reassemblying and re-use of formwork become one of the alternatif selection for the type of formwork. Analysis of the formwork subject to service load (self weight and impact load) is compulsory to avoid unexpected failure. Selection of the best construction method and site conditioning according to the design, especially for pouring the concrete in a sloping area, is very crucial since it does not only influence time construction, but also type of material, equipment, and service load during the construction. Analysis method used was comparing service load (self weight and impact load) to scaffolding capacity provided by the manufacture. Keywords: scaffolding, pipe support, horry beamPermalink: http://www.ejournal.undip.ac.id/index.php/mkts/article/view/3929[How to cite: Sumargo dan Nata, A.R., 2006, Keruntuhan Perancah Scaffolding  Saat  Pelaksanaan Pengecoran, Jurnal Media Komunikasi Teknik Sipil, Volume 14, Nomor 1, pp. 1-12]